Wpływ bezpośrednich inwestycji zagranicznych na sektor bankowy w Polsce - Polak, Waldemar (The Influence of Foreign Direct Investments on Bank Sector in Poland, 2006)
The inflow of foreign investments into Poland banks supports their modernization and stimulates their development. Foreign banks reinforce Polish economy and foreign investors extort the reduction of both costs and profits of domestic banks. Profits realized from direct investments, expected by the investor, decide conclusively on the involvement of equity capital. This paper analyses the influence of foreign direct investments on the bank sector in Poland.The inflow of foreign investments into Poland banks supports their modernization and stimulates their development. Foreign banks reinforce Polish economy and foreign investors extort the reduction of both costs and profits of domestic banks. Profits realized from direct investments, expected by the investor, decide conclusively on the involvement of equity capital. This paper analyses the influence of foreign direct investments on the bank sector in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 465-475